New fused conjugated molecules with fused thiophene and pyran units for organic electronic materials. Issue 21 (26th March 2020) - Chen, Daoliang; Zhu, Danlei; Lin, Gaobo; Du, Mingxu; Shi, Dandan; Peng, Qian; Jiang, Lang; Liu, Zitong; Zhang, Guanxin; Zhang, Deqing
Abstract : Fused conjugated molecules TTCTTC and TTTCTTTC with up to ten heterocycles were constructed by fusing fused-thiophene to the chromeno[6, 5, 4- def ]chromene unit. Abstract : Rigid and planar conjugated molecules have substantial significance due to their potential applications in organic electronics. Herein we report two highly fused ladder type conjugated molecules, TTCTTC and TTTCTTTC, with up to 10 fused rings in which the fused-thiophene rings are fused to the chromeno[6, 5, 4- def ]chromene unit. Both molecules show high HOMO levels and accordingly they can be oxidized into their radical cations with absorptions extending to 1300 nm in the presence of trifluoroacetic acid. Thin films of TTCTTC and TTTCTTTC exhibit p-type semiconductor properties with hole mobilities up to 0.39 cm 2 V −1 s −1 . Moreover, TTCTTC shows a high fluorescence quantum yield of up to 16.5% in the solid state.